LEGAL PROTECTION FOR WORKERS WHO HAVE WORK ACCIDENTS AND NOT REGISTERED IN THE BPJS PROGRAM - Benny Bambang Irawan Nitinegoro; Mahmuda Pancawisma Febriharini (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
Writing this journal aims to determine legal protection for workers who experience work accidents and are not registered in the BPJS program. In national development the role of manpower is very important, so that protection of manpower is very much needed to guarantee the basic rights of workers/laborers and guarantee equality of opportunity and treatment without discrimination on any basis to realize the welfare of workers/laborers. Guarantee of personal protection and safety and interests during the work relationship.This writing uses a normative juridical approach. The specifications for this writing are